Focused ultrasound tumour ablation in small animal oncology. (7th June 2021) - Latifi, Max; Hay, Alayna; Carroll, Jennifer; Dervisis, Nikolaos; Arnold, Lauren; Coutermarsh‐Ott, Sheryl L.; Kierski, Katharine R.; Klahn, Shawna; Allen, Irving C.; Vlaisavljevich, Eli; Tuohy, Joanne
Abstract: The cancer incidence rates for humans and animals remain high, and efforts to improve cancer treatment are crucial. Cancer treatment for solid tumours includes both treatment of the primary tumour and of metastasis. Surgery is commonly employed to resect primary and metastatic tumours, but is invasive, and is not always the optimal treatment modality. Prevention and treatment of metastatic disease often utilizes a multimodal approach, but metastasis remains a major cause of death for both human and veterinary cancer patients. Focused ultrasound (FUS) tumour ablation techniques represent a novel non‐invasive approach to treating cancer. FUS ablation is precise, thus sparing adjacent critical structures while ablating the tumour. FUS ablation can occur in a thermal or non‐thermal fashion. Thermal FUS ablation, also known as high intensity focused ultrasound (HIFU) ablation, destroys tumour cells via heat, whereas non‐thermal FUS, known as histotripsy, ablates tumour cells via mechanical disintegration of tissue. Not only can HIFU and histotripsy ablate tumours, they also demonstrate potential to upregulate the host immune system towards an anti‐tumour response. The aim of this report is provide a description of HIFU and histotripsy tumour ablation, with a focus on the basic principles of their ablation mechanisms and their clinical applicability in the field of veterinary oncology.